The Effectiveness Of Small Group Discussion Method On Reading Comprehension At The Tenth Grade SMA Negeri 1 Jasinga - Muhammad Khoerul Hadist; Al Juska Sasni Akbar; Hidjanah; Ana Ratnasari; Siti Nadiatul Husna (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2023)
The purpose of the study was to determine the application of the Small Group Discussion Technique to students' reading comprehension learning and to determine the impact of small group discussion on students' reading comprehension learning at Tenth Grade SMA Negri 1 Jasinga. The population taken was the tenth grades students of SMA Negeri 1 Jasinga and the sample was class X.4 and X.9. The design of research was experimental research. In collecting the data, the writer used pre-test and post-test. To find the significance of the study from experiment class and control class, the writer used Normality test and T-test. The research findings indicate that t-test > t-table (5,3 >1,99) It meant Ho was rejected and HI was accepted. The data showed that student’s mean score in post-test for Experimental class (74,21) was higher than in Control class (59,61). Based on the result of this research, it can be concluded there were effectiveness of small group discussion on reading comprehension at the tenth grade of SMA Negeri 1 Jasinga.